Preparation and Characterization of Hydrophobin 4-Coated Liposomes for Doxorubicin Delivery to Cancer Cells - Fatma Hande Osmanagaoglu; Aysegul Ekmekcioglu; Busel Ozcan; Gunseli Bayram Akcapinar; Meltem Muftuoglu (MDPI AG, 2024)
Background: The properties of nanoparticle surfaces are crucial in influencing their interaction with biological environments, as well as their stability, biocompatibility, targeting abilities, and cellular uptake. Hydrophobin 4 (HFB4) is a class II HFB protein produced by filamentous fungi that has a natural ability to self-assemble at hydrophobic-hydrophilic interfaces. The biocompatible, non-toxic, biodegradable, and amphipathic properties of HFB4 render it valuable for improving the solubility and bioavailability of hydrophobic drugs. We have investigated the physicochemical properties, cellular uptake, and anticancer effects of empty and Doxorubicin (Dox)-loaded HFB4 liposomes (HFB4L) and compared them to those of PEGylated liposomes (PPL). Methods: The Pichia pastoris KM71H strain was used for HFB4 purification. Liposomes were prepared through the thin film hydration method and characterized. The cytotoxic effects of free Dox, Dox-HFB4, and Dox-PPL were assessed in MCF7 cells using the SRB Assay. Results: All formulations showed good size homogeneity and a spherical shape. The HFB4 coating enhanced the physicochemical stability of Dox-HFB4L over 60 days at 4 °C without significantly affecting Dox release from HFB4L. It increased Dox release at pH 5.4 compared to pH 7.4, indicating higher delivery of drugs into acidic tumor environments, similar to Dox-PPL. While both formulations showed increased cellular uptake compared to free Dox, they exhibited a lower anticancer effect due to the sustained release of Dox. Notably, Dox-HFB4L displayed greater cytotoxicity than Dox-PPL in MCF7 cells. Conclusions: HFB4L may offer superior benefits in terms of delivering drugs to an acidic tumor environment in a stable, non-toxic, and sustained manner.